Analysis of Room Head Leadership, Internal Supervision and Nurses' Commitment Towards Service Unit Performance - Erna Rosiyawati Maruapey; Indasah Indasah; Ratna Wardani (GLOBAL HEALTH SCIENCE GROUP, 2025)
A hospital is a health service institution that provides comprehensive individual health services, providing inpatient, outpatient and emergency care (Health Law No. 17 of 2023). To realize all of this, a hospital which is a place for health services must be able to provide professional resources . One of the resources that must be prepared to be able to provide excellent service to its clients is a nurse. Improving the performance of health workers maintenance is matter Which very important in repair efforts service health to the community in general. The purpose of the study was to determine the influence of leadership, supervision internal And commitment nurse to performance service unit in Prof Dr. Soekandar Mojokerto Regency. Design study observational with approach cross-sectional . Population all nurses at Prof Dr. Soekandar Mojosari , Mojokerto Regency as many as 294 respondents. A sample of 170 respondents with proportional technique to size . Independent variables are the leadership of the head of the room, internal supervision, and nurse commitment. The dependent variable is the performance of the service unit. The research instrument used a questionnaire that was tested for validity and reliability. The analysis used was univariate and multivariate analysis with linear regression using SPSS. Test regression linear Which done show There is connection leadership For head space (p=0.005), internal supervision (p=0.000) and employee commitment (p=0.019) on employee performance. Multivariate analysis shows that the influential variable is internal supervision with a significance level of p=0.000 and B=0.188 The results of the research conducted are expected to provide input to hospitals to improve leadership by adapting to conditions. hospitals through internal supervision and performance improvement to optimize the quality of hospital services in the eyes of the public.